Libraries as Contestation Arena of the Stakeholders to Achieve Their Goals - Luki Wijayanti (Insaniyat : Journal of Islam and Humanities, 2019)
The management of university libraries in Indonesia has been intervened from foreign institutions through a donation of library materials which seem for the benefit of the academic community, but it is for the benefit of the donors. Academicians, especially the young generation, are a target of donation whether as the readers of books donated to the University or as the audience of programs or activities funded by donor agencies. Based on the background, it is found how the library becomes an arena for the contestation of various interests through some “corners” build inside the University Libraries.  Using the concepts introduced by Pierre Bourdieu such as arena and capitals. Supported by Vincent Mosco’s theory of political economy of communication as the tools of analysis, this research reveals how the agents involved in the management of the “Corner” use the library as an "arena" to achieve their benefits. The data obtained were grouped based on the sub-theme of types capital, commodification, specialization and structuration Using phenomenological approach, it is found that Corners in the university Libraries are used as an arena of contestation of agents involved in governance to foster capital. Contestation in this study illustrates the phenomenon of actors involved in the management of Corner into the dominant-subordinate relationship.